Service Life Prediction of Exterior Plastics Vision for the Future - White, Christopher C.; Martin, Jon; Chapin, J. Thomas (Springer International Publishing : Imprint: Springer, 2015)
This book defines the current state-of-the-art for predicting the lifetime of plastics exposed to weather and outlines future research needed to advance this important field of study. Coverage includes progress in developing new science and test methods to determine how materials respond to weather exposure. This book is ideal for researchers and professionals working in the field of service life prediction. This book also: Examines numerous consensus standards that affect commercial products allowing readers to see the future of standards related to service life prediction Provides the scientific foundation for the latest commercially viable instruments Presents groundbreaking research, including the blueprint of a new test method that will significantly shorten the service life prediction process time Covers two of the latest verified predictive models, which demonstrate realized-potential to transform the field.